Root knot nematode infections promoted by agricultural practice modifications in Vietnam and the impacts on rice production - Hue, Nguyen Thi; Masson, Anne -Sophie; Moulin, Lionel; Phap, Trinh Quang; Cuong, Ha Viet; Bellafiore, Stephane (Academia Journal of Biology, 2020)
A survey conducted on newly cultivated lowland rice fields by direct seeding method in Hai Duong Province, Viet Nam, in March 2017 revealed high devastation of the field. In these fields, farmers used an annual crop rotation cycle of rice-scallion-rice. Investigations on the devastated fields revealed that the chemical and physical soil properties were appropriate for rice cultivation. On the other hand, observations done on the root systems showed that the dead plants have symptomatic root galls suggesting the presence of plant parasitic nematodes. Sequencing of the internal transcribed spacer (ITS) region of the rDNA genes of the nematodes showed that the root nematodes extracted from the infested fields belonged to Meloidogyne graminicola. The reproductive factor of the isolated M. graminicola population on the IR64 rice variety (Oryza sativa indica) was normal, suggesting that the impact of this plant pest was not due to the emergence of an unusual virulent population. The combination of the three factors (wrong cropping choice for rotation, using rice variety susceptible to M. graminicola and direct seeding) were obviously promoting the nematode infection and its high proliferation in the surveyed fields. Meloidogyne graminicola could parasitize and propagate in scallions of Vietnam. Since this plant is annually cultivated on a paddy field for crop rotation, preventive measures or alternative plant for crop rottion is necessary.